2013
DOI: 10.1017/s0022377813000809
|View full text |Cite
|
Sign up to set email alerts
|

Plasmons carrying orbital angular momentum in quantum plasmas

Abstract: The existence of plasmons with orbital angular momentum due to the Laguerre-Gaussian-type density and potential perturbations is studied in an unmagnetized quantum plasma. Starting from appropriate hydrodynamic equations for the electrostatic electron dynamics, a dispersion equation is derived in paraxial approximation. The Laguerre-Gaussian beam solutions are obtained and the properties of electric field components, energy flux, and corresponding angular momentum density of plasmons are investigated. The elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…They showed that quantum mechanical effects as well as LG mode functions significantly alter the spectrum of the waves and their growth rates. In particular, Khan et al examined the impact of electron degenerate pressure on the profiles of twisted plasmons by deriving a paraxial equation in terms of density fluctuations in a strongly degenerate dense plasma. The modified expressions for electrostatic potential, energy flux, and angular momentum density were computed, which were found have significant variations through the radial and angular mode numbers.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that quantum mechanical effects as well as LG mode functions significantly alter the spectrum of the waves and their growth rates. In particular, Khan et al examined the impact of electron degenerate pressure on the profiles of twisted plasmons by deriving a paraxial equation in terms of density fluctuations in a strongly degenerate dense plasma. The modified expressions for electrostatic potential, energy flux, and angular momentum density were computed, which were found have significant variations through the radial and angular mode numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Mendonca et al. also investigated electron plasma waves carrying orbital angular momentum in an unmagnetized collisionless plasma (Mendonca, Ali & Thidé 2009 a ; Mendonca 2012) and quantum plasmas (Khan, Ali & Mendonca 2013). One knows that the electron plasma waves can be described by a paraxial equation (Mendonca et al.…”
Section: Introductionmentioning
confidence: 99%
“…Mendonca et al investigated the exchange of angular momentum between electromagnetic and electrostatic waves in stimulated Raman and Brillouin backscattering processes in plasma (Mendonca, Thidé & Then 2009b) and showed that there is conservation of the angular momentum in the laser-plasma interaction. Mendonca et al also investigated electron plasma waves carrying orbital angular momentum in an unmagnetized collisionless plasma (Mendonca, Ali & Thidé 2009a;Mendonca 2012) and quantum plasmas (Khan, Ali & Mendonca 2013). One knows that the electron plasma waves can be described by a paraxial equation (Mendonca et al 2009a,b), which is like the optical beams being described by the Helmholtz equation in the paraxial approximation.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, we used a sectional model to simulate the growth of nanoparticles in a RF acetylene discharge, which self-consistently coupled to a plasma fluid model, including a solution of Poisson's equation for the electric field. In recent years, the quantum hydrodynamics model has received wide attention for the important applications in laser-plasmas, [17] thin metal films, [18] and electrons in metals. [19] However, compared to the quantum hydrodynamics model, the fluid model has the advantages of short time consumption and high precision, which is of important for nanoparticle formation.…”
Section: Theoretical Modelmentioning
confidence: 99%